Opioid-free anesthesia reduces the severity of acute postoperative motion-induced pain and patient-controlled epidural analgesia-related adverse events in lung surgery: randomized clinical trial - Wang, Shuwei; Li, Yi; Liang, Chao; Han, Xiaodan; Wang, Jiaxing; Miao, Changhong (Frontiers in Medicine, 2023)
Background: Opioids have been used as pain relievers for thousands of years. However, they may also cause undesirable side effects. We therefore performed this study to compare the effect of opioid-free anesthesia (OFA) vs opioid-sparing anesthesia (OSA) on postoperative pain and patient-controlled epidural analgesia (PCEA)-related events. Methods: This is a single center randomized clinical trial that was recruited patients aged from 18 to 70 years who received video-assisted lung surgery between October 2021 and February 2022. Participants were 1:1 randomly assigned to OFA or OSA. Patients in the OFA group received propofol, rocuronium, esmolol, lidocaine, and magnesium sulfate intravenously with epidural ropivacaine. Patients in the OSA group received propofol, rocuronium, remifentanil, and sufentanil intravenously with epidural hydromorphone and ropivacaine. Results: A total number of 124 patients were randomly allocated to the OFA or OSA group. In the OFA group, the severity of pain during coughs on the first postoperative days (PODs) (VAS score 1.88 ± 0.88 vs 2.16± 1.1, P = 0.044) was significantly lower than that in the OSA group. The total ratio of PCEA-related adverse events in the OFA group [11(19.6%) vs 26 (47.3%), P=0.003] was significantly lower than in the OSA group. Conclusions: OFA in patients who received video-assisted lung surgery led to lower severity of acute postoperative motion-induced pain and fewer PCEA-related adverse events on the first POD than in the patients in the OSA group. Trial registration: NCT 05063396.